1997
DOI: 10.1079/bjn19970163
|View full text |Cite
|
Sign up to set email alerts
|

Influence of dietary protein and fat on serum lipids and metabolism of essential fatty acids in rats

Abstract: A 120 d feeding study with adult rats was conducted to evaluate the inhence of two protein sources (casein and gelatin), two protein levels (50 and 300g/kg diet) and two fat levels (50 and 150g/kg diet) on serum lipids (total cholesterol, HDL-cholesterol and triacylglycerols) and liver polyunsaturated fatty acid levels. In general, the concentrations of serum triacylglycerols and total cholesterol and liver phospholipid levels of arachidonic acid (AA) and docosahexaenoic acid (DHA) were higher in rats fed on c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
16
0

Year Published

2000
2000
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(20 citation statements)
references
References 20 publications
4
16
0
Order By: Relevance
“…They observed that TAG levels were inversely correlated with plasma total hydroxyproline, total glycine and total proline concentrations, three major amino acids derived from low-molecular-weight collagen fish peptides ( 21 ) . Hafidi et al ( 46 ) and Ratnayake et al ( 47 ) have also reported a decrease in TAG levels following a diet rich in glycine in rats fed a high-sucrose diet, suggesting that glycine could have contributed to the observed TAG-lowering effects following the consumption of the FG broth in this study. The lower lysine:arginine ratio of fish protein and gelatine compared with casein may also have been involved ( 48 ) .…”
Section: Discussionsupporting
confidence: 67%
“…They observed that TAG levels were inversely correlated with plasma total hydroxyproline, total glycine and total proline concentrations, three major amino acids derived from low-molecular-weight collagen fish peptides ( 21 ) . Hafidi et al ( 46 ) and Ratnayake et al ( 47 ) have also reported a decrease in TAG levels following a diet rich in glycine in rats fed a high-sucrose diet, suggesting that glycine could have contributed to the observed TAG-lowering effects following the consumption of the FG broth in this study. The lower lysine:arginine ratio of fish protein and gelatine compared with casein may also have been involved ( 48 ) .…”
Section: Discussionsupporting
confidence: 67%
“…Another group has attributed the lowering effect on plasma cholesterol and triglycerides (TGs) of gelatin, compared with casein, to its high glycine content (40). This group showed that gelatin, which contains 12 times more glycine than casein, decreases plasma cholesterol and TGs when administered in the diet of hypercholesterolemic rats.…”
mentioning
confidence: 99%
“…It has also been reported that ingestion of diets containing gelatin or CP affects the blood levels of triglycerides (TG) and/or total cholesterol (TC) in rats (Ratnayake et al, 1997;Wu et al, 2004;Saito et al, 2009), mice (Oliveira et al, 2001), and rabbits (Terpstra et al, 1983). TG and TC both decreased more markedly in rats fed a gelatincontaining diet than in rats fed a casein diet when a high protein content diet (300 g/kg diet) was used (Ratnayake et al, 1997). Oliveira et al (2001) reported that TG, but not TC, decreased significantly when mice were fed a 10% casein + 10% gelatin diet, compared with a 20% casein diet.…”
Section: Introductionmentioning
confidence: 99%